Transcriptomics and proteomics reveal a cooperation between interferon and T-helper 17 cells in neuromyelitis optica - Agnieshka M. Agasing (Nature Portfolio, 2020)
Type I IFN has apposing effects in neuromyelitis optica spectrum disorder (NMOSD) and multiple sclerosis (MS). Here the authors perform molecular profiling of NMOSD patients and mouse mechanistic experiments of neuro-inflammation to show that IFN-I stimulates pathogenic Th17 via IL-6 production by B cells.